THE RELATIONSHIP BETWEEN CONSUMPTION PATTERNS AND NUTRITIONAL STATUS IN ELEMENTARY SCHOOL-AGED CHILDREN IN THE COASTAL AREA OF SIBOLGA CITY IN 2021 - Meiyati Simatupang; Herlina Herlina; Hemro Simamora (Institute of Computer Science (IOCS), 2022)
Children of primary school age in coastal areas are among the groups at high risk of experiencing nutritional status problems. Children need adequate nutrients because they are still in their infancy. Adequate diet and consumption of nutrients are very influential for the optimal process of growth, development, and health of children. The purpose of this study was to analyze the relationship between consumption patterns and nutritional status in elementary school-age children in the coastal area of Sibolga City. The study design used a cross sectional design. The sampling technique uses the Multistage Random Sampling technique (n=259). The results of the study There was an association between dietary consumption patterns and the nutritional status of school-age children with a significance value of 0.000. The conclusion is that there is a meaningful relationship between the diet and the nutritional status of the students. Advice for the health department is expected to create health education programs in schools. Advice for puskesmas is expected to be able to hold regular measurements of student nutritional status, conduct health checks. For the nursing profession, it is expected to be able to provide education and counseling to parents and students related to the prevention of nutritional status problems in students.